2002
DOI: 10.1111/j.1749-7345.2002.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Litopenaeus vannamei Postlarvae to Low Salinity: Influence of Age, Salinity Endpoint, and Rate of Salinity Reduction

Abstract: Abstract.— Inland culture of Liropenaeus vannarnei in low salinity well waters is currently conducted on a small scale in a few areas in the U.S. To successfully rear shrimp in low salinity water, postlarvae (PL) must be transferred from high‐salinity larval rearing systems to low‐salinity growout conditions. To determine effective transfer methods, a series of experiments were conducted under controlled conditions to evaluate the influence of PL age, rate of acclimation, and salinity endpoint on 48 h survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 11 publications
4
66
0
6
Order By: Relevance
“…This is in agreement with the result obtained by Palafox et al (1997) and Perez -Velazquez et al (2007). Mcgraw et al (2002) reported that the longer salinities adjustment period could also result in better survival rate. Chen et al (1995) studied the survival, growth and osmolality of the haemolymph and the water content in the tissues of Fenneropenaeus chinensis juveniles, concluding that the osmolality of the haemolymph increased with an increase in salinity, and decreased with an increase in temperature.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the result obtained by Palafox et al (1997) and Perez -Velazquez et al (2007). Mcgraw et al (2002) reported that the longer salinities adjustment period could also result in better survival rate. Chen et al (1995) studied the survival, growth and osmolality of the haemolymph and the water content in the tissues of Fenneropenaeus chinensis juveniles, concluding that the osmolality of the haemolymph increased with an increase in salinity, and decreased with an increase in temperature.…”
Section: Discussionsupporting
confidence: 93%
“…In addition Zhu et al (2004) studied the effect of Na/K ratio on growth of L. vannamei juveniles, and stated that at higher salinities the rate of Na increased and affected the growth. This result is in agreement with the known fact that at lower salinity higher growth rate is observed (Menz and Blake, 1980;Pante, 1990;Bray et al, 1994;Somochaet et al, 1998;and McGraw et al, 2002). Menz and Blake (1980) and Bray et al (1994) reported that the L. vannamei is a euryhaline species that can tolerate a wide range of salinities (0.5-45 gL-1).…”
Section: Discussionsupporting
confidence: 89%
“…In general, the survival observed in culture systems without water exchange and in association with bioflocs is high (McAbee et al, 2003;Wasielesky et al, 2006;Kuhn et al, 2008). However, the survival of marine shrimp reared at low salinities varies and may be influenced by factors such as the ionic composition of the water, the species, the age of the animals, the rate of reduction of salinity and the final salinity at which acclimation occurs (McGraw et al, 2002;Cheng et al, 2006). In this study, shrimp survival was significantly affected by salinity, with increasing mortality as the salinity decreased from 32 to 16 and 4‰.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent animal-performance characteristics of L. vannamei, together with its tolerance of a wide range of salinities, have made this species attractive for culture at low salinities in several American countries (McGraw et al, 2002), Thailand (Saoud et al, 2003), Israel (Boyd, 2001) and China (Cheng et al, 2006). The production of marine shrimp in inland waters is more economically viable than marine shrimp culture in coastal zones due to the high cost of land and the strict environmental protection legislation in these coastal regions (Atwood et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that it is possible to successfully grow L. vannamei in low salinity waters 20 . However, survival in the early stages of rearing is largely dependent on acclimation to low salinity conditions 15 . Postlarvae (PL) purchased from commercial hatcheries are usually shipped at high salinities.…”
Section: Introductionmentioning
confidence: 99%